Optimization of Type 36 Unit Size on Apartment Occupant Satisfaction (Case Study: Asn Pasar Jumat Flats) - Mochamad Hartono; James E.D Rilatupa; Aryantono Martowardjojo (Riviera Publishing, 2025)
This study aims to assess the suitability of Type 36-unit sizes in meeting stakeholder satisfaction at the ASN Pasar Jumat Flat and proposes strategic design optimizations to improve quality of life outcomes. Space optimization is defined as maximizing functional utility through efficient layouts, multifunctional furniture, and enhancements in operational elements such as ventilation and lighting, without altering the main structure. Stakeholder satisfaction is measured based on key performance indicators (KPIs) of comfort, mobility space, storage capacity, privacy, and environmental health, assessed through standardized questionnaires. The study employs a qualitative approach, focusing on in-depth interviews to understand end-user experiences with Type 36 units. Open-ended questionnaires complement the interviews to identify satisfaction drivers, while physical measurements verify reported spatial conditions. Data from these three methods are thematically analyzed to generate actionable insights for design optimization. Findings indicate that Type 36 units fall short of stakeholder expectations in mobility space, storage, and ventilation. Layout efficiency, natural lighting, and privacy are also hindered by dimensional constraints. The study proposes strategic optimizations through spatial reconfiguration, deploying foldable or built-in furniture, and targeted improvements in ventilation and lighting. The research provides evidence-based recommendations for managers and policymakers, including adaptive design frameworks and phased renovation protocols, to enhance housing standards for ASN, particularly at the ASN Pasar Jumat Flat, and as a benchmark for future residential developments.